Comparative perfonnance of menthol mint (Mentha arvensis L. f. piperascens Malinvaud ex Holmes) cultivars in semi-arid tropical climate - Ramesh, Kamla Singh, B R Rajeswara Rao, C P Singh, P N Kaul, Gopal R Mallavarapl, S (Journal of Spices and Aromatic Crops, 2002)
Biomass yield, quantity and quality of essential oil of three menthol mint (Mentha arvensis f. piperascens) cultivars namely, Kosi, Shivalik and Himalaya grown in red sandy Joam (alfisol) soil in semi-arid tropical climate of South India, were compared. Cultivars Kosi (15.9 t ha-1) and Shivalik (15.4 t ha-1) recorded similar biomass, which were superior to that of cultivar Himalaya (14.1 t ha-1). Cultivar Kosi produced the highest essential oil yield (140.5 kg ha-1), which was 16.6% and 31.1% higher than the yields of cultivars Shivalik (120.4 kg ha-1) and Himalaya (107.2 kg ha-1), respectively. All the three cultivars yielded good quality essential oils having menthol (77.2% in cv. Kosi; 76.3% in cv. Shivalik; 75.5% in cv Himalaya) as their main constituent. Based on the result, cultivar Kosi is highly promising for commercial cultivation in red soils in the semiarid tropical climate of South India.